Pengelolaan Kesehatan Keluarga Secara Mandiri Melalui Pemanfaatan Tanaman Toga Di RW 04 Kelurahan Putat Gede Kecamatan Sukomanunggal Surabaya - Ely Tjahjani; Lina Darmayanti Bainuan; Endang Buda Setyowati (Pelita Abdi Masyarakat, 2021)
Background : Increasing human resources in health development through community empowerment can be realized through community participation, one of which is the planting of TOGA (Family Medicine Park). Planting TOGA in the home environment is very important, especially for families in carrying out initial treatment before going to health services. This community service activity is Community Empowerment in utilizing TOGA plants which begins with licensing, observation and socialization. Based on field observations, most of the people in RW 4, Putat Gede sub-district (90.20%) do not have family medicinal plants. Therefore, it is necessary to conduct socialization or counseling about the benefits and efficacy of TOGA so that people have knowledge and are encouraged to plant TOGA. Methods : The target of this service activity is the community of RT 02 and RT 05 RW 04, Putat Gede village. The purpose of this community service is that it is hoped that the community can know and utilize various kinds of TOGA plants and provide motivation for the importance of planting TOGA. Results : The results obtained by socializing the use of TOGA to 45 people there was an increase in participants' knowledge, the average pretest was 65.08 and post-test was 79.99 and TOGA was planted in the RW hall as a pilot. Conclusion : Counseling given to the community provides an increase in the community's ability to use TOGA